A giant metanephric adenoma in a young male. Issue 4 (11th April 2023) - Mremi, Alex; Bodganowics, Jack; Sadiq, Adnan; Tadayo, Joshua; Lodhia, Jay
Abstract: Metanephric adenoma is an uncommon renal tumor with almost exclusively benign behavior, which can clinically and radiologically imitate malignancy. The histological examination is therefore crucial in diagnosis. Herein, we report a case of an 18-year-old male with a huge left renal mass. Histopathology and immunohistochemistry of nephrectomy resection specimen confirmed it to be metanephric adenoma. We present our experience with this rare tumor entity and literature review with focusing on differential diagnosis.